2021
DOI: 10.3390/jcm10235479
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral and Systemic Stress Parameters in Correlation with Jugulo-Arterial CO2 Gap as a Marker of Cerebral Perfusion during Carotid Endarterectomy

Abstract: Intraoperative stress is common to patients undergoing carotid endarterectomy (CEA); thus, impaired oxygen and metabolic balance may appear. In this study, we aimed to identify new markers of intraoperative cerebral ischemia, with predictive value on postoperative complications during CEA, performed in regional anesthesia. A total of 54 patients with significant carotid stenosis were recruited and submitted to CEA. Jugular and arterial blood samples were taken four times during operation, to measure the jugulo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…S100B is able to cross into the bloodstream[23]. Consequently, serum S100B levels can indicate the presence and extent of neural damage, serving as a specific biomarker for evaluating the neuroprotective effects of SGB on brain tissue[24][25][26][27]. Sago et al reported that the release of proinflammatory cytokines interleukin (IL)-8 and IL-6 is heightened during cellular hypoxia[28].…”
mentioning
confidence: 99%
“…S100B is able to cross into the bloodstream[23]. Consequently, serum S100B levels can indicate the presence and extent of neural damage, serving as a specific biomarker for evaluating the neuroprotective effects of SGB on brain tissue[24][25][26][27]. Sago et al reported that the release of proinflammatory cytokines interleukin (IL)-8 and IL-6 is heightened during cellular hypoxia[28].…”
mentioning
confidence: 99%